Analysis of Hotel Harper's Revenue Increase on the Regional Original Revenue of Medan City - Edi Suprayetno; Abdiyanto Abdiyanto; Dewi Mahrani Rangkuty (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study aims to analyse the increase in Harper Hotel revenue to Medan City's local revenue. There is a dependent variable, namely the Regional Original Revenue of Medan City, and two independent variables, namely lodging and other hotel revenue. This research uses primary data by conducting direct data searches on the management of Harper Hotel. The data analysis model in this study uses multiple linear regression. The results showed that the Lodging Revenue and Other Revenue Variables had a significant effect on Regional Original Revenue in Medan City.